Chronic obstructive pulmonary disease 7: Management of COPD. Issue 3 (1st March 2003) - MacNee, W; Calverley, P M A
Abstract : A review of the management of COPD is presented, with particular emphasis on the effect on the approach to management of new information which has become available in the 5 years since the BTS guidelines on COPD were published. A major problem is the effective implementation of what is already known, and allocation of the resources necessary to make this available to all who might benefit.